CHARACTERIZATION OF AN ALKYLAMMONIUM-MONTMORILLONITE-PHENANTHRENE INTERCALATION COMPLEX BY CARBON-13 NUCLEAR MAGNETIC RESONANCE SPECTROSCOPY - Theng B.K.G.; Whitton J.S.; Newman R.H. (My University, 1998)
Low molecular weight polycyclic aromatic hydrocarbons can intercalate from the solid phase into montmorillonite (Mt) saturated with quaternary alkylammonium ions. However, the interaction and relationship between guest and host organic molecules in the interlayer space of the clay are not well understood. We have intercalated phenanthrene into tetradecyltrimethylammonium (TDTMA)-montmorillonite by a solid-solid reaction. The basal spacing of the original TDTMA-Mt complex is close to 1.8 nm, indicating the presence in the interlayer space of a double layer of TDTMA ions with the alkyl (polymethylene) chains lying parallel to the silicate layers, and the carbon zig-zags adopting an all-trans conformation. After intercalation of phenanthrene the basal spacing increases to about 3.4 nm, indicating a change in orientation of the alkyl chains with respect to the silicate layers. 13C-NMR spectroscopy shows that adding phenanthrene to TDTMA-Mt leads to a displacement by -3 ppm of the -(CH2)n- signal for TDTMA. This signal and that for interlayer phenantbrene are also broadened relative to the respective pure compounds. These observations, together with measurements of nuclear spin relaxation time constants, strongly suggest that in the complex with phenanthrene the polymethylene chains of TDTMA extend away from the silicate layers, and no longer assume a rigid all-trans carbon zig-zag conformation. Rather, the TDTMA chains become relatively disordered and intimately mixed with phenanthrene.